2019
DOI: 10.26444/aaem/99669
|View full text |Cite
|
Sign up to set email alerts
|

Protective antigen domain 4 of <i>Bacillus anthracis</i> as a candidate for use as vaccine for anthrax

Abstract: Protective antigen domain 4 of Bacillus anthracis as a candidate for use as vaccine for anthrax.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
(18 reference statements)
0
7
0
1
Order By: Relevance
“…Thus, Oliveira et al [42], investigating the kinetic laws of success and the reasons for the inability of embryos to reach the blastocyst stage, obtained the maximum percentage of blastocyst yield -29.9%. While in Stoliarova and Leontieva [43], using KSOM medium with the addition of 1 mM glutamine and bovine serum albumin at a concentration of 1 mg/cm 3 , this indicator was 22.3%. According to the study results, the use of the bovine embryo cultivation protocol, both Minitube and Origio, which was not previously used for the cultivation of bovine embryos, the percentage of division and the percentage of obtained embryos were within the data presented by other scientists [42; 43].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, Oliveira et al [42], investigating the kinetic laws of success and the reasons for the inability of embryos to reach the blastocyst stage, obtained the maximum percentage of blastocyst yield -29.9%. While in Stoliarova and Leontieva [43], using KSOM medium with the addition of 1 mM glutamine and bovine serum albumin at a concentration of 1 mg/cm 3 , this indicator was 22.3%. According to the study results, the use of the bovine embryo cultivation protocol, both Minitube and Origio, which was not previously used for the cultivation of bovine embryos, the percentage of division and the percentage of obtained embryos were within the data presented by other scientists [42; 43].…”
Section: Resultsmentioning
confidence: 97%
“…Although it has been used for decades, some fundamental properties of AVP are understudied, including its exact composition and which proteins other than PA may contribute to protection. Recent studies have shown [42][43][44] that the effectiveness of AVP in humans may depend not only on PA. Firstly, there is strong evidence that LF plays a protective role, and computational predictions suggest that added proteins may be important in individuals with specific combinations of HLA alleles [43; 45; 46]. Secondly, despite the differences in the sequences of key antigenic proteins in different strains of B. anthracis, it is unlikely that they will affect the crossstrain protection provided by AVP [47][48][49].…”
Section: Literature Reviewmentioning
confidence: 99%
“…W tym czasie w ośrodku realizowano wiele ambitnych zadań, wykorzystując zarówno doświadczoną kadrę mikrobiologów, pracowników przeszkolonych w USA, jak również przyjętych do pracy biotechnologów, których szkolono intensywnie w technikach identyfikacji mikroorganizmów z zastosowaniem metod biologii molekularnej oraz technik klonowania, w tym heterologicznej ekspresji i separacji białek immunogennych [14,15]. Zwieńczeniem wieloletniej współpracy z USA była wizyta ambasadora Victora Ashe (2005 r.), który osobiście zapoznał się z imponującymi efektami współdziałania ośrodka z US Army w dziedzinie obrony przed bronią biologiczną, szybką diagnostyką, udziałem przedstawicieli ośrodka w alianckich misjach w Iraku oraz wynikami szkolenia personelu w USA.…”
Section: Zagrożenia Bioterrorystyczne Po 11 Września 2001 Runclassified
“…In Poland, the State Health Inspectorate has developed plans to counteract crisis situations, in particular bioterrorist attacks, and procedures to deal with specific situations: eg, rules for notification and cooperation in the event of a threat of a dangerous infectious disease or bioterrorism, a scheme for dealing with suspicious shipments, and procedures for dealing with cases of smallpox, anthrax, and botulism. 44 Twenty-five hospitals have also been appointed to care for patients with particularly dangerous infectious diseases, as well as transport units for the evacuation of these patients, and 10 laboratories of provincial health and epidemiological stations, which have been proposed for inclusion in the NATO network of reference laboratories. [45][46][47] Smallpox vaccines have been purchased with funds budgeted for the Minister of Health and lists of persons from particular risk groups to be vaccinated in the event of an emergency have been prepared.…”
Section: Conclusion and Potential For The Futurementioning
confidence: 99%